Technology-mediated learning in physiotherapy education: The social construction of practice knowledge - J. Frantz; M. Rowe (AOSIS, 2013)
Clinical practice is complex, requiring practitioners to interpret adiverse range of inter-related variables in order to make clinical decisions as part ofpatient management. This process is often intuitive and therefore hidden from studentsand less experienced clinicians, making the cognitive processes that inform clinicaldecision-making difficult to learn. In addition, educators still emphasise the learningof knowledge and skills through didactic teaching methods, such as lectures, in whichstudents are passive "recipients" of knowledge. Unless physiotherapy educators designactivities that aim to induct students into the professional culture and help them todevelop ways of thinking and being that go beyond knowledge and skills, our studentswill continue to struggle with clinical reasoning.In this position paper, we argue that the careful integration of technology as an adjunct to traditional lectures can be usedto facilitate discussion and interaction as a way of developing practice knowledge in students. This leads to higher cognitivefunctioning as it provides the means by which learners construct their own personally meaningful understanding of the worldthrough interaction with others. The promise of technology in physiotherapy education lies in its ability to create transformativelearning experiences through enhanced communication that is mediated by more experienced teachers or peers. If technology isused to enhance the learning environment by providing richer and more meaningful platforms for communication and discussion,it may have a role to play in the social construction of knowledge as part of contextualised learning spaces.